Lost in transition: labour market entry sequences of school leavers in Europe - Christian Brzinsky-Fay (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2006)
In the paper I examine sequences of school-to-work transitions in ten European countries by using explorative methods of optimal matching and cluster analysis. The process of labour market entry is observed for the five years following departure from school by examining monthly labour market statuses. The sequences are classified by similarity, and certain sequence types along with their distribution are described. The resulting picture shows strong variation across countries, which can only partly be captured by classic typologies of school-to-work transition regimes. Apart from that, the quality of the coordination process between the educational system and the labour market can be assessed by taking into account indicators derived from the TLM concept, namely, volatility, integrative capability and the degree of risk. – – Das vorliegende Papier untersucht Übergangssequenzen von der Schule in den Beruf in zehn europäischen Ländern unter Verwendung explorativer Methoden wie optimal matching und Clusteranalyse. Der Prozess der Arbeitsmarktintegration wird anhand der monatlichen Arbeitsmarkzustände in den ersten fünf Jahren nach Verlassen der Schule beobachtet. Die Übergangssequenzen werden nach ihrer Ähnlichkeit gruppiert und hinsichtlich ihrer Verteilung beschrieben. Im Ergebnis zeigt sich, dass diese Übergangssequenzen beachtlich zwischen den europäischen Ländern variieren, was nur teilweise durch klassische Typologien von Übergangsregimen erklärt werden kann. Zusätzlich wird die Qualität des Koordinierungsprozesses zwischen Bildungssystem und Arbeitsmarkt anhand von Indikatoren beurteilt, die aus dem Konzept der Übergangsarbeitsmärkte abgeleitet wurden. Hierbei handelt es sich um die Volatilität, die Integrationsfähigkeit und den Risikocharakter von Übergangssequenzen.
Keywords: 330